Non-Nepenthes Carnivorous Plants in Indonesia: Current Knowledge on Diversity, Ethnobotany, and Phytochemistry - Wendy A. Mustaqim (Jurnal Biologi Tropis, 2021)
One of the most unique plant groups in the world is carnivorous plants. Indonesia is home to many species of this plant group. Nepenthaceae, represented by single genus Nepenthes, is relatively well known, but the others are not. A literature study and several field trips were conducted to give a summary of the diversity and the potential uses of the non-Nepenthes carnivorous plants in Indonesia. Three families with a total number of 29 species have been reported for Indonesia, namely Lentibulariaceae (20 species), Droseraceae (8 species), and Byblidaceae (1 species). One species, Aldrovanda vesiculosa is listed as Endangered based on IUCN Red List. The results reveal that several species possess ethnobotanical and medicinal uses as well as other potential such as in phytoremediation and nanoparticle biosynthesis. Several bioactivities have been reported such as anticancer, antihypertensive, antitumor, antioxidant, antibacterial, or even hepatoprotective. Among the most important bioactivity is anticancer which is supported by the presence of secondary metabolites named plumbagin, which so far has been found in three species. Our result indicates that this plant group is highly potential and warrants further studies and or development.